2022
DOI: 10.3389/fmed.2022.816822
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Urinary Biomarker in the Common Mechanism of Physical Performance and Cognitive Function

Abstract: IntroductionHealthy aging is described as a process of developing and maintaining intrinsic abilities, including physical and cognitive functions. Although oxidative stress is a common mechanism shared by loss of muscle strength and dementia, its relationship with decreased physical performance and cognitive impairment remains unclear. We aimed to investigate the role of urinary 8-oxo-7, 8-dihydroguanosine (8-oxoGsn), a biomarker of oxidative damage to RNA, in physical and cognitive decline.MethodsThe study fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The European muti-centre MARK-AGE study analysed biomarkers in more than 2000 older adults and found lower levels of antioxidants, including β-cryptoxanthin and zeaxanthin, in those who were physically, cognitively, or psychologically frail (Rietman, Spijkerman, et al, 2019). Jiang et al, (2022) found that a urinary biomarker, 8-oxoGsn, was associated with poor physical performance and worse cognitive function, relationships persisting once several confounders including age were controlled for, suggesting levels may be a useful indicator for early screening for MCI in frail patients and could be used to determine efficacy of anti-oxidative stress interventions.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The European muti-centre MARK-AGE study analysed biomarkers in more than 2000 older adults and found lower levels of antioxidants, including β-cryptoxanthin and zeaxanthin, in those who were physically, cognitively, or psychologically frail (Rietman, Spijkerman, et al, 2019). Jiang et al, (2022) found that a urinary biomarker, 8-oxoGsn, was associated with poor physical performance and worse cognitive function, relationships persisting once several confounders including age were controlled for, suggesting levels may be a useful indicator for early screening for MCI in frail patients and could be used to determine efficacy of anti-oxidative stress interventions.…”
Section: Resultsmentioning
confidence: 97%
“…(Rietman, Spijkerman, et al, 2019). Jiang et al, (2022) found that a urinary biomarker, 8-oxoGsn, was associated with poor physical performance and worse cognitive function, relationships persisting once several confounders including age were controlled for, suggesting levels may be a useful indicator for early screening for MCI in frail patients and could be used to determine efficacy of anti-oxidative stress interventions.…”
Section: Dietary Choices and Nutritionmentioning
confidence: 99%
“…8-Hydroxyguanosine 8-Hydroxyguanosine (8-oxo(d)G) is an extensively studied product of nucleic acid oxidation formed by guanine oxidation, disrupting DNA pairing and causing gene mutations [79,83]. 8-oxoGsn, a metabolite reflecting oxidative damage to RNA, plays a significant role in heart disease through its association with oxidative stress [83][84][85][86]. Elevated levels of urinary 8-oxoGsn, indicative of RNA oxidative damage, have been linked to poor physical performance and cognitive impairment, suggesting a relationship between oxidative stress and a decline in these functions, which are also common in heart disease [83,84].…”
Section: Myeloperoxidasementioning
confidence: 99%
“…Therefore, urinary 8-oxoGsn may serve as a valuable biomarker for assessing oxidative damage and evaluating the progression of heart disease. However, further research is needed to confirm these findings and establish causality, as well as to identify associated risk factors and determine the utility of urinary 8-oxoGsn in clinical practice for managing heart disease [85,87]. 6.2.6.…”
Section: Myeloperoxidasementioning
confidence: 99%